Three Dimensional Printed Immunomodulatory Scaffolds with Controlled Drug Release for Bone Regeneration - Majrashi, Majed (2023)
Large bone defects pose significant challenges in orthopaedic surgery, necessitating the exploration of innovative repair technologies beyond traditional treatments like autografts, allografts, and synthetic substitutes, each fraught with specific challenges. Tissue engineering and regenerative medicine have emerged as promising fields, employing bioactive materials, growth factors, and cellular components to emulate natural bone properties and functions. Notably, additive manufacturing techniques contribute to these advancements by customising 3D-printed scaffolds enhancing patient-specific treatments.